DESENVOLVIMENTO DE UM CASO SIMULADO CTS NO ENSINO DE FUNÇÕES ORGÂNICAS - Kuchla, Micheli (2016)
This dissertation has as a purpose of study develop a didactic guide for the teaching organic functions of. This study aimed, work in one simulated case, relating to reality of the student in an approach of science, technology and society. For the application of the simulated case, was utilized like a didactic resource the simulated jury, where involves a discussion about the implementation of a one textile industry of the city. The work was realized with the students of the third year nightly of high school of two schools of the stadual net of teaching, one at Prudentópolis-Pr and another in Guamiranga-Pr. This research is characterized like qualitative. For the data collect was utilized the diary of camp and the observation of the participant. Another way of the collect data was the formation of an one group of press by the students, and was applied too questionnaires searching for the students opinions in relation of the proposed activity. The activities were divided in three moments with nine activities at the total, in which seeked establish social relations of science and technology. The simulated case showed like excellent ally, because brought a bigger contribution for the critic formation of the students, once that permited a wide discussion and per interfere directly in your reality. Other result reached comprises the elaboration of one didactic guide which have for objective, share activities developed in this study, like a methodological suggestion for the professionals who teaching chemistry and acting in the high school.